A preliminary exploration of the development of integrated psychotherapy and pastoral counseling among the American Christian psychologists and pastoral psycho-therapists: A qualitative systematic literature review - Chai Foong Lee; Jamayah Saili; Keezrawati Mujan Yusuf (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας)
This systematic literature review paper aims to broadly trace the development of integrated psychotherapy and pastoral counseling from the advent of Freudian psychoanalytic theory in 1900 to the present day. Following the PRISMA (Preferred Reporting Items for Systematic Reviews) guidelines, an electronic search of journals in congruence with the research objectives was conducted from Sage, Scopus and Google Scholar. This search resulted in 2408 related reviewed papers being considered (Scopus: 534; Sage: 719; Google Scholar: 1155). Through the process of eliminating duplicates, screening relevant titles, abstracts, full text and stringent inclusive and exclusive criteria, 31 reviewed papers were selected. A thematic synthesis of extracted data resulted in identifying three broad categories of: When (Time/Stage of the integrative effort); What (Definition/Defining Moment of the integrative stage); and How & Why (The Influences of the Time and the Pace setters of the Hour). This paper covers an era of integrative work spanning over almost one and a quarter centuries. As the integrative progress evolves with time, this paper also endeavors to identify the underlying reasons sustaining this century-long quest and research.